2014
DOI: 10.1136/jmedgenet-2013-101943
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the phenotype of mutations in DICER1: mosaic missense mutations in the RNase IIIb domain ofDICER1cause GLOW syndrome

Abstract: Background Constitutional DICER1 mutations have been associated with pleuropulmonary blastoma, cystic nephroma, Sertoli-Leydig tumours and multinodular goitres, while somatic DICER1 mutations have been reported in additional tumour types. Here we report a novel syndrome termed GLOW, an acronym for its core phenotypic findings, which include Global developmental delay, Lung cysts, Overgrowth and Wilms tumour caused by mutations in the RNase IIIb domain of DICER1. Methods and results We performed whole exome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 34 publications
6
71
0
Order By: Relevance
“…Of note, mosaic DICER1 mutations in our cases and the two previously described cases7 are localised to the sequence encoding the RNase IIIb domain. We have also identified additional likely pathogenic second somatic mutations or LOH in the tumours.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Of note, mosaic DICER1 mutations in our cases and the two previously described cases7 are localised to the sequence encoding the RNase IIIb domain. We have also identified additional likely pathogenic second somatic mutations or LOH in the tumours.…”
Section: Discussionsupporting
confidence: 63%
“…DICER1 syndrome has autosomal-dominant inheritance with variable penetrance and may present from infancy through adolescence and occasionally later 6. Using whole-exome sequencing, Klein et al 7 have recently reported mosaic missense mutations in DICER1 , affecting the RNase IIIb metal-ion binding domain, in peripheral blood DNA from two infants; allele frequencies were 21% and 28%, respectively. Each infant had extensive bilateral lung cysts consistent radiographically with cystic PPB, developed bilateral Wilms tumour (in one child in large kidneys with underlying renal dysmorphology) and had global developmental delays and various overgrowth stigmata.…”
Section: Introductionmentioning
confidence: 99%
“…DICER1 pathogenic variants may also be associated with macrocephaly (17). An overgrowth syndrome has been reported in some children where the pathogenic variants are mosaic and affect the RNase IIIb domain (18). PPB presents in four main forms (19).…”
Section: Dicer1 Syndromementioning
confidence: 99%
“…These individuals may display earlier diagnosis of DICER1-related conditions, have a higher number of sites of disease, and warrant more intensive surveillance. Mosaic RNase IIIb domain pathogenic variants are the likely basis of GLOW syndrome (Global developmental delay, Lung cysts, Overgrowth and Wilms tumor), which is a more severe form of DICER1 syndrome (18).…”
Section: Dicer1 Syndromementioning
confidence: 99%
“…We consider this mutation deleterious because i) it has not been reported before (ExAC, EVS, ClinVar), ii) it lies one residue away from the metal ion binding residue 1813, and iii) has a defect in miRNA processing. The clinical phenotype, however, associated with this mutation appears to be somewhat milder than the very severe phenotypes that are associated with either germline or mosaic RNase IIIb mutations that directly impinge on metal ion binding residues (de Kock et al 2014, Klein et al 2014, emphasizing the need for full characterization of previously unreported DICER1 variants. This requires a combined approach involving pathology, genetics, biochemistry, and molecular modeling.…”
mentioning
confidence: 99%